Meta-Analysis: The Effect of Discovery Learning Models on Students' Mathematical Ability - Khairunnisa, Khairunnisa; Juandi, Dadang (Jurnal Riset Pendidikan Matematika, 2022)
This research aims to determine the magnitude of the influence of the discovery learning model on students' mathematical abilities. These included problem-solving skills, critical thinking, understanding, and mathematical reasoning. This study employs a quantitative approach with a Meta-Analysis method. Data collected was from experimental research connected to the application of discovery learning models to the mathematical abilities of elementary, junior high school, and high school students in papers indexed from 2012 to 2021. From the search and study selection results, 48 articles were obtained. The findings found an annual increase in the number of publications, most of which were on mathematical reasoning abilities. Researchers also conducted more research at the junior high school education level, with a sample size of more than 30. Meanwhile, when viewed from the demographic aspect, this study is more located on the island of Java. The application of the discovery learning model to students' mathematical abilities has an overall effect size of 0.815 with the high effect category.